(untitled) (Marketing Journal, 2025)
The article examines the issues of the influence of marketing activities on the formation of the efficiency of management of internal subsystems of economic entities: production, investment and innovation activities, personnel, finance, and resource manage ment. In addition, the article examines the economic efficiency of investments in marketing research - growth of net profit, net cash flow and value of company.